Preventing Social Sites from Publishing Malicious Content (International Journal of Engineering and Computer Science, 2018)
The World Wide Web has become an inseparable part of millions of people who use online services e.g. online banking, online shopping, social networking, e-commerce, and store and manage user sensitive information, etc. In fact, it is a popular tool for any class of user over the Internet. Rich Web based applications are available over the World Wide Web to provide such types of services. At the same time, the Web has become an important means for people to interact with each other and do business. This is the positive side of this technology. Because the Web can also become a most dangerous place. Due to popularity of World Wide Web which has also attracted intruders and attackers to harm network services.   These intruders abuse the  users and internet by performing illegitimate activity for their financial profit. These Web pages that contain such types of malicious code are called as malicious Web pages.